Remnant Trees Affect Species Composition but Not Structure of Tropical Second-Growth Forest - Sandor, Manette E. (Public Library of Science, 2014)
Remnant trees, spared from cutting when tropical forests are cleared for agriculture or grazing, act as nuclei of forest regeneration following field abandonment. Previous studies on remnant trees were primarily conducted in active pasture or old fields abandoned in the previous 2–3 years, and focused on structure and species richness of regenerating forest, but not species composition. Our study is among the first to investigate the effects of remnant trees on neighborhood forest structure, biodiversity, and species composition 20 years post-abandonment. We compared the woody vegetation around individual remnant trees to nearby plots without remnant trees in the same second-growth forests (“control plots”). Forest structure beneath remnant trees did not differ significantly from control plots. Species richness and species diversity were significantly higher around remnant trees. The species composition around remnant trees differed significantly from control plots and more closely resembled the species composition of nearby old-growth forest. The proportion of old-growth specialists and generalists around remnant trees was significantly greater than in control plots. Although previous studies show that remnant trees may initially accelerate secondary forest growth, we found no evidence that they locally affect stem density, basal area, and seedling density at later stages of regrowth. Remnant trees do, however, have a clear effect on the species diversity, composition, and ecological groups of the surrounding woody vegetation, even after 20 years of forest regeneration. To accelerate the return of diversity and old-growth forest species into regrowing forest on abandoned land, landowners should be encouraged to retain remnant trees in agricultural or pastoral fields.